2014
DOI: 10.1103/physreve.90.062121
|View full text |Cite
|
Sign up to set email alerts
|

Interference of identical particles and the quantum work distribution

Abstract: Quantum-mechanical particles in a confining potential interfere with each other while undergoing thermodynamic processes far from thermal equilibrium. By evaluating the corresponding transition probabilities between many-particle eigenstates we obtain the quantum work distribution function for identical bosons and fermions, which we compare with the case of distinguishable particles. We find that the quantum work distributions for bosons and fermions significantly differ at low temperatures, while, as expected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 91 publications
1
42
0
1
Order By: Relevance
“…Finally, to determine the time evolved density operator we further require the proper two particle evolution operator. It can be shown that in energy representation the two particle propagator is the symmetric (for bosons) or antisymmetric (for fermions) linear combination of single particle propagators [71]. The same is true in position representation (see Appendix B for a full derivation),…”
Section: Preliminariesmentioning
confidence: 85%
“…Finally, to determine the time evolved density operator we further require the proper two particle evolution operator. It can be shown that in energy representation the two particle propagator is the symmetric (for bosons) or antisymmetric (for fermions) linear combination of single particle propagators [71]. The same is true in position representation (see Appendix B for a full derivation),…”
Section: Preliminariesmentioning
confidence: 85%
“…In the context of quantum thermal machines, the interplay between statistics and engine performance needs more study [158,219]. This is crucial since typical work fluids of quantum thermal machines constitute several particles.…”
Section: Discussion and Open Questionsmentioning
confidence: 99%
“…Nevertheless, for quantum many-body systems, the correspondence between quantum and classical work distributions has not been studied so far. The indistinguishability of identical particles [27,28] and the interaction makes the properties of quantum work even more elusive. Also, the nonequilibrium dynamic evolution of a quantum manybody system is extremely difficult to solve.…”
Section: Introductionmentioning
confidence: 99%